Utilizing Different Drying Techniques for Preparing Banana Center Core Flour - Gaurav Kumar (International Journal of Modern Agriculture, 2021)
Banana center core has been utilized as vegetables in the Indian culinary of south India. Endeavors have been developed to build up the technique for preparation the banana center core flour because of its powerful usage due to joining into nourishment. Banana center core dices was dried by various techniques such as, drying in the sun, sunlight based drying as well as plate drying at 50 and 70 degrees Celsius temperature individually. The banana place core dices that were first dried were then changed over to flour in pound with the end goal 90% powder went by 400-micron sifter. The impact of banana’s practical and physical properties place core flour by drying was broke down. Consequences of investigation indicated that flour acquired by drying center core dices of banana at 70 Degree Celsius in a plate was good in terms of the quality contrasted with various techniques.